2012
DOI: 10.1097/meg.0b013e3283524d32
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization confers survival benefit in patients with a spontaneously ruptured hepatocellular carcinoma

Abstract: TACE is a minimally invasive treatment that has a high success rate for hemostasis. TACE increased the 30-day survival in patients with a ruptured HCC. However, survival rates in patients with lower hemoglobin levels, resulting in a large amount of bleeding, remained poor regardless of successful TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…It was reported that TAE for a ruptured HCC resulted in better prognosis than patients who underwent conservative treatment (MST: 110 vs. 9.0 days, P < 0.003) [6]. In our study, patients with a ruptured HCC treated curatively showed better prognosis than those not treated curatively (22.7 vs. 1.8 months, P < 0.001).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…It was reported that TAE for a ruptured HCC resulted in better prognosis than patients who underwent conservative treatment (MST: 110 vs. 9.0 days, P < 0.003) [6]. In our study, patients with a ruptured HCC treated curatively showed better prognosis than those not treated curatively (22.7 vs. 1.8 months, P < 0.001).…”
Section: Discussionsupporting
confidence: 44%
“…The mortality rate associated with a ruptured HCC in the acute phase has been reported to range from 25% to 75% [2]. Furthermore, the 1-month survival rate of patients with a ruptured HCC has been found to range from 35% to 67% [6,7]. Miyoshi et al reported that the mortality rate with 1 year was 40% and MST was 10 months [8].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HCC rupture has decreased to approximately 3-15%, probably in response to advances in imaging modalities and the development of a surveillance system for patients infected with HBV or HCV; however, mortality rates remain high [21,22]. Even if surgical resection is performed, the median survival duration is only 1.1 years, and the prognosis is very poor [23].…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Interestingly, shock was not significantly related to survival, concordant with previous publication. 17 The present investigation also revealed increased mortality in the setting of lobar embolisation, advocating for more selective embolisation when feasible.…”
Section: Resultsmentioning
confidence: 87%